PSYCHOLOGICAL ASPECTS OF DEVELOPMENT OF COORDINATION BETWEEN 6-8 YEARS OLD CHILDREN’S MUSICAL HEARING AND VOCAL APPARATUS - Davidova, Jelena; Zavadska, Galina; Rauduvaite, Asta; Chuang, Ming-Jen (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
In the present article, the psychological aspects of the development and process of coordination between 6-8 years old children’s musical hearing and vocal apparatus are considered, among which an important role is played by such cognitive processes as music perception, representation of musical hearing, musical thinking, musical memory and self-control. This research aims at studying the psychological aspects of the process of coordination of musical hearing and vocal apparatus between 6-8 years old children.